Tinjauan Pembaharuan Pendidikan Islam di Indonesia - Mardinal Tarigan; Imelda Manurung; Naila Anugrah (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Renewing Islamic education in Indonesia is the main focus in facing changing times. This article explores the renewal of Islamic education from historical and contemporary perspectives, highlighting the background, methodology, results and thoughts of key figures. The research method uses a literature study and literature study approach, with data collection through electronic sources such as Google Scholar and digital libraries. The results of the research outline the concept of Islamic education reform, the background to the reform in the 19th and 20th centuries, and the influence of the reform on Islamic education in Indonesia. The main focus is on the thoughts of reformer figures such as Muhammad Abduh and Rasyid Ridha, who pushed back to the teachings of the Koran and Al-Hadith, the spirit of nationalism, and local factors. Renewing Islamic education in Indonesia includes the integration of digital literacy, critical thinking skills, improving infrastructure, and strengthening the values ​​of tolerance. This article also identifies approaches to renewing Islamic education, ranging from Western orientation to Islamic orientation and nationalism. Thus, the renewal of Islamic education in Indonesia is a continuous effort to improve the quality of education, strengthen Islamic identity, and prepare a generation that is ready to compete globally.